PENGARUH TAKARAN PUPUK BATUAN FOSFAT TERHADAP PERTUMBUHAN PEREPAT (Combretocarpus rotundatus Miq) DIINOKULASI MIKORIZA PADA MEDIA GAMBUT - Burhanuddin (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2012)
The purpose of the study to determine the dosage of phosphate rock fertilizer to enhance growth Combretocarpus rotundatus Miq with arbuscular mycorrhizal fungi inoculated. Seedbed experiment using factorial completely randomized design with three replications. Observations were made on seedling age perepat 14 weeks after weaning, including: height, diameter, leaf number, and for shoot dry weight, P uptake of plants after harvest. Experimental tests on C.rotundatus Miq and phosphat fertilizer inoculated with arbuscular mycorrhizal fungi to prove that the dose of phosphate rock 100 ppm was the best increase C.rotundatus Miq growth in the nursery. Keywords : Peat soil, Mycorrhyza, Combretocarpus rotundatus, Phosphate rocks